Case Report: 3D imaging-assisted minimally-invasive hybrid closure surgery of a complex coronary artery fistulas - Chen, Yu; Lu, Jin; Lian, Xingchen; Chang, Peipei; Wen, Ping; Ma, Lin; Liu, Yuhang (Frontiers in Cardiovascular Medicine, 2024)
Coronary artery fistulas (CAFs) are rare congenital heart defects that are typically managed through interventional closure, traditional surgery, or minimally invasive hybrid closure surgery. However, treating CAFs with complex anatomy, such as tortuous vessels, presents a significant challenge, particularly in young children. We report the case of a 3.8-year-old child (15 kg/100 cm) with a complex CAF, treated using a minimally invasive hybrid closure surgery approach with a 4 × 4 mm Amplatzer Duct Occluder II (ADO II) (Abbott, USA). Three-dimensional (3D) imaging was utilized to visualize the CAF's anatomy, guide the surgical planning, and accurately determine the puncture site on the right ventricular free wall, as well as the optimal sheath direction and insertion depth. The procedure was carried out efficiently and safely, guided by preoperative 3D imaging and intraoperative transesophageal echocardiography. Follow-up at one year demonstrated excellent outcomes with no complications.